PENGARUH SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI E-WORD OF MOUTH PADA GIVANDA STORE DENPASAR - Ni Made Puspita Dewi; I Gusti Ayu Imbayani; Pande Ketut Ribek (VALUES, 2021)
The use of the internet in Indonesia is dominated by the use of social media, this is what has made the growth of e-marketing where the practice of marketing through social media is used as a product marketing tool to promote a company's brand and brand. One of them is Givanda Store Denpasar, which chooses to market its products through social media, but the sales that have been realized have not reached the expected target, because there is a lot of competition in sales through social media. This study aims to test and obtain empirical evidence of the influence of social media marketing and e-word of mouth on purchasing decisions, social media marketing on e-word of mouth and the influence of social media marketing on purchasing decisions mediated by e-word of mouth at Givanda Store. Denpasar. The population in this study were all consumers of Givanda Store Denpasar whose number was unknown or infinite, the number of samples was determined using the Roscoe method so that 120 people were used as samples, and samples were taken using random sampling techniques. The analytical tool used is path analysis using Partial Least Square (PLS). The results of this study indicate that social media marketing has a positive effect on purchasing decisions at Givanda Store Denpasar, social media marketing has a positive effect on e-word of mouth at Givanda Store Denpasar, e-word of mouth has a positive effect on purchasing decisions at Givanda Store Denpasar, and e-word of mouth is able to mediate the relationship between social media marketing and purchasing decisions at Givanda Store Denpasar. It is suggested to Givanda Store Denpasar to look for new forms of promotion, for example giving discounts to consumers so that consumers always shop at Givanda Store Denpasar.